Geocentric Datum GDM2000 for Malaysia: implementation and implications - A. K., Abd. Majid; Ses, Sahrum; Mohd Omar, Kamaludin; Omar, Abdullah Hisham; Abu, Samad; Nordin, Soeb (2003)

(untitled)
The Department of Survey and Mapping Malaysia (DSMM), in collaboration with the Universiti Teknologi Malaysia(UTM), has carried out a study towards the establishment of a new geodetic framework for the country. The new Geocentric Datum for Malaysia (GDM2000) is being built by GPS space geodetic technology based on International Terresterial Reference Frame (ITRF2000) and Geodetic Reference System 1980 (GRS80) reference ellipsoid. GDM2000 is connected to ITRF2000 by the inclusion of 15 International GPS Service (IGS) sites from the nearby regions in the precise baselines processing and adjustment of a network of existing Malaysian Active GPS System (MASS) stations. The process of implementing GDM2000 in particular matters related to datum transformation and map projection is being addressed. New sets of transformation parameters concerning conversion from the existing local datum to the new GDM2000 have been developed. Its implication on the existing cadastral and mapping practices, various GPS non-mapping applications, and GIS/LIS related applications have been considered. In addition to that, its socio-economic implications on the implimentation of GDM2000 is also presented. Majid Kadir, Shahrum Ses, Kamaludin Omar, Ghazali Desa and Abdullah Hisam Omar